A Need Analysis of Learning Listening based on the Online Quizizz Application at English Language Education Department of Universitas Sembilanbelas November Kolaka - Netty Huzniati Andas; Karman Karman (EduLine: Journal of Education and Learning Innovation, 2022)
The aim of this study was to find out students’ needs on learning listening based on Online Quizizz at USN Kolaka. There were two kinds of instruments used in this study namely a close-ended questionnaire and an interview guide line. The questionnaire was distributed to 51 students of English Language Education Department USN Kolaka and two students were interviewed for further information. Six components of need analysis were assessed in this study namely students’ lack, students’ goal, input, procedure, learners’ roles, and teacher’s roles. It was found out that most students need to improve their listening skills which aim to crack the TOEFL score. They prefer to do the Quizizz listening exercises individually with students’ total control on the listening exercises. They need to have 2-4 chances of giving their best shot on the exercises within one week. They do not like being timed when answering the questions, and also background sound is off.